The Human Y Chromosome: The Biological Role of a "Functional Wasteland". Issue 1 (15th September 2000) - Quintana-Murci, Lluís; Fellous, Marc
Abstract : "Functional wasteland, " "Nonrecombining desert" and "Gene-poor chromosome" are only some examples of the different definitions given to the Y chromosome in the last decade. In comparison to the other chromosomes, the Y is poor in genes, being more than 50% of its sequence composed of repeated elements. Moreover, the Y genes are in continuous decay probably due to the lack of recombination of this chromosome. But the human Y chromosome, at the same time, plays a central role in human biology. The presence or absence of this chromosome determines gonadal sex. Thus, mammalian embryos with a Y chromosome develop testes, while those without it develop ovaries (Polani [38]). What is responsible for the male phenotype is the testis-determining SRY gene (Sinclair [52]) which remains the most distinguishing characteristic of this chromosome. In addition to SRY, the presence of other genes with important functions has been reported, including a region associated to Turner estigmata, a gene related to the development of gonadoblastoma and, most important, genes related to germ cell development and maintenance and then, related with male fertility (Lahn and Page [31]). This paper reviews the structure and the biological functions of this peculiar chromosome.